The Capability of Tyramine Production and Correlation between Phenotypic and Genetic Characteristics of Enterococcus faecium and Enterococcus faecalis Strains - Bargossi, Eleonora; Gardini, Fausto; Gatto, Veronica; Montanari, Chiara; Torriani, Sandra; Tabanelli, Giulia (Frontiers in Microbiology, 2015)
The aim of this study was to investigate the diversity of tyramine production capability of four Enterococcus strains in buffered systems in relation to their genetic characteristics and environmental conditions. Cells of the strains Enterococcus faecalis EF37 and ATCC 29212, and Enterococcus faecium FC12 and FC643 were re-suspended in phosphate/citrate buffers with different pH, NaCl concentration and incubation temperature. At intervals, cell viability and tyramine production were assessed by plate counting and HPLC analysis, respectively. The activity of a purified tyrosine decarboxylase (TDC) was determined under the same conditions, as a reference. Reduced loss in cell viability was observed in all the tested conditions, except for pH 4 after 24 h. The TDC activity was greatly heterogeneous within the enterococci: EF37 and FC12 produced the higher tyramine concentrations, ATCC 29212 showed a reduced decarboxylase activity, while EF643 did not accumulate detectable amounts of tyramine in all the conditions assayed. Among the considerate variables, temperature was the most influencing factor on tyramine accumulation for enterococcal cells. To further correlate the phenotypic and genetic characteristics of the enterococci, the TDC operon region carrying the genes tyrosine decarboxylase (tyrDC), tyrosine/tyramine permease (tyrP), and Na+/H+ antiporter (nhaC-2) was amplified and sequenced. The genetic organization and nucleotide sequence of this operon region were highly conserved in the enterococcal strains of the same species. The heterogeneity in tyramine production found between the two E. faecalis strains could be ascribed to different regulation mechanisms not yet elucidated. On the contrary, a codon stop was identified in the translated tyrDC sequence of E. faecium FC643, supporting its inability to accumulate tyramine in the tested conditions. In addition, the presence of an additional putative tyrosine decarboxylase with different substrate specificity and genetic organization was noticed for the first time. Concluding, the high TDC activity heterogeneity within enterococci determined different accumulation of tyramine, depending on different genetic determinants, regulation mechanisms and environmental factors. The present research contributes to elucidate the genetic characteristics of enterococcal strains and correlate specific mutations to their different strain-dependent tyraminogenic activity.